Molecular Characterization of Cyclophilin Protein Gene in Skin Normal Microflora: Malassezia furfur - M Moazeni; F Noorbakhsh; F Zaini; P Kordbacheh; J Hashemi; B Mousavi; L Andonian; S Rezaie (Tehran University of Medical Sciences, 2009)
Background: Malassezia are dimorphic, lipid-dependent yeasts, which are responsible for causing several cutaneous and systemic conditions. Although cyclophilins (CyPs) are highly conserved cytosolic proteins that catalyze the peptidyl-prolyl cis-trans isomerazation reaction before protein folding process, it has been suggestive of an allergen in a few numbers of fungi such as Aspergillus fumigatus and Malassezia species. Allergenic cyclophilins are IgE-binding components, which have been characterized in other species of Malassezia; and are considered as Mala s 6 in Malassezia sympodialis.  In the present study we tried to identify the molecular characterization of cyclophilin gene in M. furfur. Methods: Pairs of oligonucleotide primers were designed from highly conserved regions of the gene counterparts in other fungi. The primers were then applied to amplify the primer-specific DNA fragment. Afterward, PCR product fragments were sequenced to be used in further analysis. Results: About 573 nucleotides, encoding a polypeptide of 190 amino acids, have been sequenced. Sequence comparison was performed in Gene Bank, both for the nucleotides and their deduced amino acid sequence. It revealed a significant homology with cyclophilin genes and proteins of other eukaryotic cells. The amino acid sequence of the encoded protein was about 86% identical to the sequence of cyclophilin protein from other fungi. Conclusion: The molecular characterization of cyclophilin gene may open the way to disclosure of the functional characteristics of cyclophilin and is a fundamental step for understanding the molecular basis of its pathogenesis in AEDS disease.